REDUCING HOSPITAL OUTPATIENT WAITING TIME USING LEAN SIX SIGMA: A SYSTEMATIC REVIEW - Elina Waiman; Anhari Achadi; Renita Agustina (Indonesian Journal of Health Administration, 2023)
Background: Lean Six Sigma (LSS) is a beneficial data-driven tool for quality improvement. Literature regarding the use of LSS to reduce hospital outpatient waiting time is scarce despite numerous problems encountered in many countries. Aims: This systematic review aims to evaluate the causes of long outpatient waiting time, demonstrate the effectiveness of LSS and the improvement strategies applied to reduce outpatient waiting time. Methods: Literature search was performed on eight databases: Proquest, Wiley, Science Direct, Taylor and Francis, Oxford Journal, Sage Publication, Scopus, and Pubmed. Inclusion criteria were peer-reviewed English articles published from January 1, 2003, to May 25, 2021, and studies conducted in hospital settings. Results: Nine relevant articles were included. Inefficient clinic processes, inappropriate scheduling, human resources problems, workplace factors, patient communication problems, and patient characteristics are root causes found for long outpatient waiting time. All studies revealed a reduction in outpatient waiting time (5.2% to 97%) after implementation of LSS. Process redesign, improvement in appointment scheduling, patient communication, and improvement in workplace design, were strategies used to reduce outpatient waiting time. These strategies increase the number of patients seen and hospital gross revenue, as well as patient satisfaction. Conclusion: LSS is beneficial to reduce outpatient waiting time. Process redesign provide advantageous results. Keywords: hospital, lean six sigma, outpatient waiting time, process redesign